Reflections by a member of the Editorial Board - Kevin T. Smith (Les)
I thank Co-Editors Ass. Prof. Dr. Jože Kropivšek and Prof. Dr. Katarina Čufar for the opportunity to serve as an Editorial Board member of Les/Wood, an international journal firmly grounded in the broad sweep of Slovene wood science and technology. The Editorial Board works to extend the relevance and impact of Les/Wood within and beyond Slovenia to the international community of wood science and technology in the broadest sense. We see the journal as a tool to support research and development of specific technologies, as well as to develop common terminology.